Comparing levels of subsistence stress amongst Norse settlers in Iceland and Greenland using levels of bone fat exploitation as an indicator - Outram, Alan K (Environmental Archaeology, 2003)
Reproduced with permission of the publisher. Copyright © Oxbow Books and the Association for Environmental Archaeology 2003. The background to the Icelandic and Greenlandic sites under investigation is outlined and prior work on the Norse economies of the two islands is discussed. The importance of fat in the diet and the use of levels of bone marrow and grease exploitation as an indicator of subsistence stress are explained. The methodology for establishing levels of bone fat exploitation is outlined. This methodology involves the detailed study of fragmentation levels of different types of bone, study of bone fracture types and many other taphonomic indicators. The results of the study are described and discussed. On Greenland, the Norse inhabitants exploited almost all available fat from land mammal bones, leaving only the ribs. lt is argued that this indicates a severe level of subsistence stress amongst the Greenlanders that is most likely related to a seasonal dearth in resources. On lceland, whilst a certain amount of bone marrow is almost certainly exploited, the settlers appear to almost totally ignore the potential to exploit bone grease. This is likely to be indicative of a much more healthy subsistence economy than on Greenland. These results are discussed in relation to differing climate, availability of good soil, fishing practices and seasonal rounds.